The Eschatological Spirituality of “the Sons of Light” in Qumran - Wróbel, Mirosław Stanisław (Verbum Vitae, 2020)
One of the most important features of the members of the Qumran community, who referred to themselves by the name “the sons of light,” was aspiration to holiness by observing the Law, purity and cult. The spirituality of the Qumran community was founded on the New Covenant which would be fulfilled “at the end of the days”. This eschatological reality was stressed in the practical spirituality of the members of the Qumran community. In the present article, the spirituality of the Qumran community will be presented via three points: (1) The origin of the Qumran community; (2) The community of a New Covenant with God; and (3) Eschatological beliefs. Our accumulated knowledge about the spirituality of the Qumran community and its beliefs enables us to better understand many eschatological texts of the Old Testament and Intertestamental Literature. It also indicates to us certain similarities and differences with the teachings of Jesus of Nazareth.